BALANCING SELF-FULFILLMENT AND COMMITMENT, UNPACKING THE EXTRINSIC MOTIVATION LINK - Zahid Saeed; Haslinda Abdullah; Rasika Jayatilleke (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2025)
The reason for this study is to explore the causal relationship between organizational commitment and self-fulfillment, with a particular center on the intervening part of extrinsic motivation. The objectives incorporate looking at how organizational commitment impacts both extrinsic motivation and self-fulfillment inside an organizational setting. Utilizing a quantitative approach, information was collected from individuals of the scholarly community from higher education institutions organized in Selangor to test the proposed connections. The result shows a noteworthy positive effect of organizational commitment on both extrinsic motivation and self-fulfillment. Besides, mediation analysis uncovers that extrinsic motivation partially mediates the relationship between organizational commitment and self-fulfillment, recommending that whereas organizational commitment specifically improves self-fulfillment, it too does so in an indirect way by boosting extrinsic motivation. These discoveries emphasize the significance of cultivating an organizational commitment to upgrade worker inspiration and individual fulfillment, highlighting the requirement for organizations to create situations that bolster commitment and inspiration in their workforce.